Government department to public corporation in a deregulated economy: The economic efficiency of New Zealand telecommunications - Boles de Boer, David; Evans, Lewis (School of Management Working Papers, 1994)
This paper estimates the productivity and consumer and producer gains of the telecommunications network market as Telecom has developed as an SOE and public company. The growth in productivity is estimated to have resulted in an annual compound average of 5.6 per cent cost reduction. The consumer gains have been substantial. They have come from price reductions on 1987 consumption levels and, to a lesser extent, from output expansion. In addition there has been marked improvement in the quality of outputs. The consumer and producer and share price analysis indicate that a deeper examination, than simply looking at a company's risk-adjusted rate of return, is required to understand the impact on economic efficiency of different organisational structures and operating environments.